FONEMIK BAHASA DAYAK MALI - Simanjuntak, Hotma (Universitas Tanjungpura, 2020)
The Mali Dayak community resides in Balai-Batang Tarang Sub-district and a small part resides in Tayan Hilir District, Sanggau District. They have the same ethnic communication language, the Mali Dayak language. As of 2008 the number of Malian Dayak speakers was estimated at 6,963 people (Bamba, 2008). Languages with fewer than 10,000 speakers are classified as endangered (Crystal, 2000). If there is no attempt to maintain this Mali Dayak language, over time, this language is heading for extinction. Therefore, even the slightesteffort to preserve this language needs to be done. This study discusses the main problems regarding the Dayak Mali phonemic, namely the determination of phonemes, allophones, phoneme distribution, phoneme groups (cluster), phoneme sequences, and syllables of the Dayak Mali language which are based on structural theory. The results of this study indicate the phonemes of the Dayak Mali language, namely vowel, diphthong, consonant, and semivocal phonemes. Based on its distribution, a phonemic allophon is apparent. Thephonemic sequence also shows the environment of mutual influence and shows the symmetrical features of the phonemes found in the Dayak language of Mali. Similarly, the consonant group, the situation is answered through this research. The last problem examined is the syllables. The syllable structure contained in the Mali Dayak language is also described.